Pemanfaatan Audio Visual sebagai Sumber dalam Pelajaran Sejarah di Madrasah Tahfizhil Quran - Puspa Unsya Shaleha; Muhammad Ricky Hardiyansyah; Muhammad Adika Nugraha; Surya Aymanda Nababan (Keguruan, 2023)
Advances in science and innovation, especially data innovation, have a tremendous impact on the planning and implementation of learning methodologies. Media are delegates such as television, radio, slides, and literature, but also include individuals as learning assets or as exercises including conversations, courses, field trips, re-enactments, etc., which are designed to increase understanding and change the student's mentality. to add information. This review uses a subjective graphic exploration strategy, with an exam area in MA Tahfizhil Quran. The main subjects in this study are history educators and students at MA Tahfizhil Quran who focus on learning exercises on Indonesian history material using audiovisuals in history learning. Considering the side effects of exploration and conversation using general media in learning Indonesian history for class The meaning of the learning material becomes clearer, making it easier for students to understand the lesson. Next, students do additional learning exercises because they don't just pay attention to the teacher's explanation; they do different exercises, for example noticing, doing, and illustrating